2015
DOI: 10.1242/jcs.172627
|View full text |Cite|
|
Sign up to set email alerts
|

The Drosophila centriole: conversion of doublets to triplets within the stem cell niche

Abstract: We report here that two distinct centriole lineages exist in Drosophila: somatic centrioles usually composed by microtubule doublets and germ line centrioles characterized by triplets. Remarkably, the transition from doublets to triplets in the testis occurs within the stem cell niche with the formation of the C-tubule. We demonstrated that the old mother centriole that stays in the apical cytoplasm of the male germline stem cells (GSCs) is invariably composed by triplets, whereas its daughter is always built … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 24 publications
2
42
0
Order By: Relevance
“…Alternatively, different SAS-6 and Bld10/Cep135 isoforms could be accommodated in centrioles without varying symmetry by changing the size of microtubule blades at the outer organelle wall in a compensatory manner. We note, for example, that D. melanogaster germ line centrioles possess a triplet of microtubules in each organelle blade, while centrioles in somatic cells have microtubule doublets [43].…”
Section: Discussionmentioning
confidence: 86%
“…Alternatively, different SAS-6 and Bld10/Cep135 isoforms could be accommodated in centrioles without varying symmetry by changing the size of microtubule blades at the outer organelle wall in a compensatory manner. We note, for example, that D. melanogaster germ line centrioles possess a triplet of microtubules in each organelle blade, while centrioles in somatic cells have microtubule doublets [43].…”
Section: Discussionmentioning
confidence: 86%
“…However, it was shown that MT doublets were present in Drosophila centriolar cylinders in somatic cells, and MT triplets were present in generative cells (Tates, 1971; Gottardo et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Another observation concerning the structural diversity of centrioles was that somatic cell centrioles in Drosophila consist of doublets and germ cell line centrioles consist of MT triplets (Gottardo et al, 2015). In the cell cycle of vertebrates there is also a stage when young procentrioles consist of MT doublets, but this stage is very short and occurs near the beginning of procentriole formation (Guichard et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic analysis of early development in these two models, which may not be representative of the most common development of Ecdysozoa, has yet been of invaluable importance for identifying the conserved core complex of gene products necessary for centriole duplication [203], as well as key regulatory activities controlling the centrosome maturation and activity at G2–M–G1 transition [207,209,213]. Yet, somatic centrioles—the situation is apparently different for basal bodies from the sperm cells in flies [243]—are not canonical in these two species, and look as simplified versions of the highly conserved centriolar structure, lacking the distal part where appendages are anchored on the mother centriole. As a matter of fact, they lack from one-third in the fly to half in the worm of gene products that are conserved in both unicellular organisms and mammalians [223].…”
Section: Fate Of Cell Polarity At the Transition To Multicellularitymentioning
confidence: 99%